Mineralogy, alteration, fluid inclusions microthermometry and genesis of the Cu-Au Kalateh Dasht deposit, south of Shahrood, NE Iran - Mohadeseh Eskandari; Fardin Mousivand; Maryam Sheibi; Bernd Lehmann (Journal of Economic Geology)
The Kalateh Dasht deposit is situated in the northern part of the Central Iran structural zone, northeast of the Toroud-Chah Shirin magmatic arc. The Cu-Au mineralization is hosted by diorite porphyry subvolcanic rocks with a post-Eocene age. The mineralization occurs in the form of hydrothermal breccia and vein-veinlet along a fault zone with an approximately N30E extension and vertical dip. Several mineralized veins consisting of pyrite, chalcopyrite, sphalerite, bornite, galena, barite, hematite, chalcocite, covellite, malachite, and chrysocolla are observed parallel to each other in this fault zone. The gangue minerals include comb quartz, crustiform, and a small amount of amethyst as veins and blades. SEM data indicate the presence of gold within sphalerite. The porphyritic diorite host rocks have been significantly altered due to the action of hydrothermal fluids, resulting in sericitic, siliceous, and propylitic alteration (chlorite, epidote, and calcite), particularly at the margins of mineralized veins. The fluid inclusions in calcite and barite host minerals reveal that homogenization temperatures range between 143.2 and 213.1ºC and salinity varies between 3.06 and 7.73 wt.% NaCl eq. In close proximity to this ore deposit, an argillic alteration zone and other mineralization systems in this region increase the likelihood of a porphyry system at greater depth.